Plan para la formación curricular de cátedras de accesibilidad en las facultades de Arquitectura en Colombia (2016)
The objective of this research paper as a product of the final work of the master by the author, entitled “Protocol for the training curriculum chairs of accessibility in the faculties of architecture in Colombia” is to present a work proposal that includes curricular formation of a chair of accessibility, by setting a systematic and flexible plan in the training process, to project the transformation of the territory by developing an accessible physical environment that contribute to respect for human rights and equal opportunities.In connection with the above, this research paper has been developed and supported from a qualitative methodological process, made up by a phase of gathering information on the various fields of accessibility and its relationship with the academy, complemented by a phase of analysis where all the results of data collection are recorded, in order to determine the synthesis phase that defines the plan of the proposal. Finally, it concludes with some suggestive considerations as route center lines for the implementation of the subject.Accessibility conditions, that urban and rural environments have historically presented, have been a constant state of exclusion and discrimination against people with disabilities, whether temporary or permanent, or at the most vulnerable population groups. This is mainly due to the physical obstacles that cities or attitudes have about citizenship.